The judges' decision is final: Judgement in music talent reality TV and school music education. Issue 3 (1st December 2019) - Butler, Alison
This article explores music talent reality television (RTV) and conceptualizes it as a site of music education. It also considers whether music talent RTV might magnify sociocultural traits that are less easily detected in other sites of music education. A considerable body of research has developed around RTV, notably from the fields of sociology, media studies, cultural studies and women's studies. These scholars frequently draw on Bourdieu's concepts of habitus and capital to analyse participant and audience engagements with the genre. Judgement is central to these discussions, particularly in the subgenre of music talent RTV, with several authors showing how taste and distinction are influenced by habitus. Reviewing the RTV literature highlights how certain musics and musicking experiences are judged, and how such judgement can devalue the musical experiences of those young people who are least likely to access school music education. This raises questions for further study about music talent RTV's relationship with school music education, and for the study of music talent RTV as a music education setting in its own right, but it also highlights themes that warrant consideration in school music education sites, where judgements and their impacts on access and participation are often disguised or unquestioned.